The Role of Philanthropy in Reducing the Negative Impact of Poverty and Natural Disasters on Economic Growth - Salman Zakki Mubarok; Edi Cahyono (Cita Konsultindo Research Center, 2024)
This study aims to examine the relationship between poverty variables to economic growth, the relationship between natural disaster variables to economic growth, moderation of philanthropic variables on the relationship between poverty and economic growth, and moderation of philanthropic variables on the relationship between natural disasters and economic growth. The object of research is the member countries of the Organisation of Islamic Cooperation (OIC). The type of research is quantitative research. Data collection methods with secondary data collection. The population in this study were 57 OIC member countries. The sampling technique used purposive sampling with a sample of 7 OIC member countries. The data used is panel data processed using Eviews 10. The model chosen is the random effect model. The results showed that poverty has a negative but insignificant effect on economic growth. In addition, the natural disaster variable has a positive but insignificant effect on economic growth. The moderating variable of philanthropy proved to be able to moderate the effect of poverty and natural disasters on economic growth.